Assessment of patterns and related factors in using social media platforms to access health and oral health information among Sri Lankan adults, with special emphasis on promoting oral health awareness - Yovanthi Anurangi Jayasinghe; Kehinde Kazeem Kanmodi; Rasika Manori Jayasinghe; Ruwan Duminda Jayasinghe (BMC, 2024)
Abstract Background Social media has evolved beyond its conventional purpose of communication and information sharing to become a potent tool for disseminating health and oral health awareness. This study seeks to assess the patterns and related factors of using social media platforms to access health and oral health information among Sri Lankan adults, with special emphasis to promotion of oral health awareness. Methods In March 2023, individuals aged ≥ 18 years residing in Sri Lanka, who are users of social media participated in this electronic questionnaire-based survey. Statistical analyses of the collected data were done using the SPSS version 21 software, with a p-value of < 0.05 set to determine the level of statistical significance. Results A total of 421 persons participated in this survey. Majority (68.4%) belonged to the age category of 18 to 30 years, and 55.5% were females. WhatsApp (96.8%) was the most frequently used social media platform across all age groups and both genders. Statistically significant differences were identified between genders in the usage of Telegram, Twitter, and Viber within the 18-30 years age category, with a higher percentage of males using these platforms (p ≤ 0.05). Similar significant differences were observed in the 31-40 years age group for WhatsApp and Telegram (p ≤ 0.05). Among 95.4% of online health information seekers, YouTube (74.9%) was the most popular platform. One-quarter of the respondents preferred social media platforms, and 22.3% preferred websites for obtaining oral health information. Furthermore, 74.9% had positive opinions on obtaining oral health information via social media, while only 17% reported pleasant experiences with social media platforms for oral health promotion. In assessing the reliability of oral health information on social media, 48% relied on the quality of the information. The most preferred source of oral health information was short videos from professionals (43.1%). Additionally, 69.5% reported changes in their oral health behaviours after accessing information through social media. Conclusion Social media is a viable platform for promoting public oral health awareness in Sri Lankan; hence, workable strategies need to be employed, to further ensure its effective and wider use in a culturally and socioeconomically diverse country like Sri Lanka.